“Análisis Jurídico, Doctrinario y de Derecho Comparado sobre la figura jurídica del divorcio ”. - Gualan Cabrera, Bryan Ricardo (2024)
The present work of curricular integration entitled "Legal, doctrinal and comparative law analysis of the legal figure of divorce" has the purpose of demonstrating that divorce in Ecuador needs an urgent normative update regarding its causes and its legal effects in the financial compensation to the affected spouse; in addition to addressing general issues regarding its regulation. To this end, a general study of all topics related to divorce was carried out, such as its historical background, its legal effects and procedures; with the purpose of carrying out a general analysis of this legal figure in terms of its regulation, use and applicability in Ecuadorian legislation. All of this is framed within the Constitution, the Ecuadorian Civil Code, the Code of Childhood and Adolescence and the General Organic Code of Processes, taking into consideration that the current regulations need an update since there are many flaws identified, therefore, it is It is necessary to modify the rules regarding the use of grounds for divorce and regarding financial compensation to the affected spouse, the obligation to establish specific rules that clearly regulate this problem. With the help of the field study regarding surveys and interviews applied to law professionals in free practice, it has been possible to verify the normative emergencies that are necessary to achieve legal stability regarding divorce and its effects. The statistical study has shown the lack of application of the grounds for divorce, and thanks to comparative law, the need to implement clear regulations regarding financial compensation to the affected spouse has been corroborated in terms of their consistent post-divorce support. , that is, he has suffered a considerable economic imbalance that does not allow him to have a decent life. The present work is concluded with the approach of propositional guidelines aimed at promoting urgent regulatory updating regarding the problem raised, as well as implementing clear regulations regarding financial compensation to the person who has been caused by the divorce. an economic imbalance.